Analysis of Digital Marketing Adoption in Indonesian Micro, Small, and Medium Enterprises - Aditya Andika; Jennifer Jennifer; Jesslyn C. Huang; Jeannette C. Sebastian (Universitas Pendidikan Nasional, 2021)
Micro, small, and medium-sized enterprises (MSMEs) have a major role in Indonesia’s economy. In order to grow, MSMEs need the capability to conduct marketing in the digital world. The advancements in digital technologies have made it possible for a cost-effective and hassle-free Digital Marketing adoption. However, the number of MSMEs that have adopted Digital Marketing is still low. Therefore, this study aims to find out what factors that affect Digital Marketing adoption and its benefits. This study will also analyze the implementation of Digital Marketing by MSMEs in Indonesia. This study uses literature study method. This study shows that there are various factors affecting Digital Marketing adoption. This study also shows that various research results have shown that Digital Marketing Adoption can improve the performance of MSMEs. In regards to Digital Marketing implementation in Indonesia’s MSMEs, this study shows that training and mentoring activities by Centers for Research and Community Service of various Higher Education Institutions in Indonesia are very beneficial for MSMEs.